2014
DOI: 10.1088/0004-637x/798/1/43
|View full text |Cite
|
Sign up to set email alerts
|

JET PROPERTIES OF GeV-SELECTED RADIO-LOUD NARROW-LINE SEYFERT 1 GALAXIES AND POSSIBLE CONNECTION TO THEIR DISK AND CORONA

Abstract: The observed spectral energy distributions of five GeV-selected narrow-line Seyfert 1 (NLS1) galaxies are fitted with a model including the radiation ingredients from the relativistic jet, the accretion disk, and the corona. We compare the properties of these GeV NLS1 galaxies with flat spectrum radio quasars (FS-RQs), BL Lacertae objects (BL Lacs) and radio-quiet (RQ) Seyfert galaxies, and explore possible hints for jet-disk/corona connection. Our results show that the radiation physics and the jet properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 81 publications
9
78
1
Order By: Relevance
“…In comparison to the SED of a typical BL Lac and FSRQ source, they found that their broad-band spectra can be regarded as intermediate between both blazar types, although they bear a closer resemblance to the SED of FSRQs. Similar results have been obtained by independent studies from Foschini et al (2015) and Sun et al (2015). Table 7.…”
Section: Foschinisupporting
confidence: 91%
“…In comparison to the SED of a typical BL Lac and FSRQ source, they found that their broad-band spectra can be regarded as intermediate between both blazar types, although they bear a closer resemblance to the SED of FSRQs. Similar results have been obtained by independent studies from Foschini et al (2015) and Sun et al (2015). Table 7.…”
Section: Foschinisupporting
confidence: 91%
“…Two scenarios were considered for the EC scattering process: a seed photon field dominated from the torus and from the BLR, respectively. The energy density of the former was assumed to be 3 × 10 −4 erg cm −3 (see more details in Cleary et al 2007;Ghisellini & Tavecchio 2008) and the latter was estimated from the broad Hβ line luminosity derived in Section 2 (see more details in Sun et al 2015;Zhang et al 2015). The energy distribution of the injected relativistic electrons was assumed to be a broken PL in the range of [γ min , γ max ] with a break energy γ b .…”
Section: Broad-band Spectral Energy Distributionmentioning
confidence: 99%
“…Along with their small SMBH masses, i.e., more rapid timescales of variability, this makes radio-loud NLS1 galaxies excellently suited for studying the disc-jet symbiosis. The black symbols represent the SED of SDSSJ1222+0413 ( [148]), while the grey symbols are measurements and models of PMN0948+0022 at different epochs, taken from [31], [132] and [46].…”
Section: Figurementioning
confidence: 99%
“…In many cases, an accretion-disc component is additionally present. The SEDs are generally well modelled with one-zone leptonic jet models with external Comptonization (e.g., [1], [2], [3], [44], [27], [28], [31], [32], [45], [46], [47], [113], [114], [115], [153], [103], [132], [147], [148], [110], [79], [146]). Based on detailed modelling of the SED of 1H0323+342, [85] concluded that the site of the γ-ray formation is located inside the BLR, and that the external Comptonization is due to seed photons from the accretion disc.…”
Section: Sed Modellingmentioning
confidence: 99%